2005
DOI: 10.1002/hep.20590
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among cardiotrophin-1, prostaglandins, and vascular endothelial growth factor in rat liver regeneration

Abstract: Prostaglandins are hepatoprotective molecules generated in liver regeneration by the rapid induction of cyclooxygenase-2 (COX-2). Cardiotrophin-1 (CT-1) and vascular endothelial growth factor (VEGF) are other hepatoprotective mediators upregulated at 24 hours after partial hepatectomy. The interactions among these molecules during liver regeneration have not yet been defined. Here we show that rats subjected to partial hepatectomy treated with NS-398, a specific COX-2 inhibitor, exhibited cell cycle arrest, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…15,16,33,37 Our results and those of other studies showed that CT-1 receptors are present in cardiac fibroblasts, VSMCs, ECs, monocytes, and macrophages. 11,[13][14][15] Several lines of evidence have shown that foam cell formation and CD36 and ACAT1 expression in macrophages and the migration and proliferation of VSMCs are mediated via ERK-1/2.…”
Section: Discussionsupporting
confidence: 83%
“…15,16,33,37 Our results and those of other studies showed that CT-1 receptors are present in cardiac fibroblasts, VSMCs, ECs, monocytes, and macrophages. 11,[13][14][15] Several lines of evidence have shown that foam cell formation and CD36 and ACAT1 expression in macrophages and the migration and proliferation of VSMCs are mediated via ERK-1/2.…”
Section: Discussionsupporting
confidence: 83%
“…Soon after its discovery, CT-1 was shown to be a potent inducer of the acute phase response in rat primary hepatocytes [2,90] and subsequent studies showed that CT-1 is an essential factor in the defense of the liver against a variety of insults [91][92][93][94][95]. In the liver CT-1 mRNA is expressed by both hepatocytes and non-parenchymal cells [94].…”
Section: Livermentioning
confidence: 97%
“…rCT-1 was obtained as described elsewhere ( 16 ) and contained <0.04 ng LPS per 1 g of the protein as determined by the Limulus amoebocyte lysate assay (Cambrex, East Rutherford, NJ).…”
Section: Rct-1mentioning
confidence: 99%